2015
DOI: 10.9738/intsurg-d-14-00176.1
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Good Perioperative Outcomes After Pancreaticoduodenectomy in a Low-Volume Setting: A 25-Year Experience

Abstract: Perioperative mortality following pancreaticoduodenectomy has improved over time and is lower than 5% in selected high-volume centers. Based on several large literature series on pancreaticoduodenectomy from high-volume centers, some defend that high annual volumes are necessary for good outcomes after pancreaticoduodenectomy. We report here the outcomes of a low annual volume pancreaticoduodenectomy series after incorporating technical expertise from a high-volume center. We included all patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…As one of the deadliest types of cancer, PDAC is commonly diagnosed in late stages and is associated with rapid progression and metastasis, resulting in the ASR for 5-year net survival less than 5% [ 5 , 6 , 19 , 20 ]. Due to the lack of effective therapy, cure is seldom considered as a treatment outcome while efforts are mainly intended to prolong the survival of PDAC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the deadliest types of cancer, PDAC is commonly diagnosed in late stages and is associated with rapid progression and metastasis, resulting in the ASR for 5-year net survival less than 5% [ 5 , 6 , 19 , 20 ]. Due to the lack of effective therapy, cure is seldom considered as a treatment outcome while efforts are mainly intended to prolong the survival of PDAC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreaticoduodenectomy (Whipple procedure) is commonly adopted to treat tumors from the head of the pancreas; whereas laparoscopic surgery is ideal to treat tumors from the tail of the pancreas [3,4]. Although advances in surgical instruments and techniques have significantly brought down the mortality rate for the pancreaticoduodenectomy procedure, the ASR for 5-year net survival remains less than 5% for PDAC patients [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…And when this concern is focused on performing pancreaticoduodenectomy (PD), which is thought to be a high-risk cancer surgery, the relationship between volume and outcome invariably increased [123456]. However, some studies concluded that experienced surgeons or incorporation of expertise from high-volume centers may achieve satisfactory outcomes after PD in low-volume centers [789].…”
Section: Introductionmentioning
confidence: 99%